Zebrafish larvae are a suitable model to investigate the metabolic phenotype of drug-induced renal tubular injury - Morello, Judit (2018)
This work was supported by the Calouste Gulbenkian Foundation, Gulbenkian Professorship 121986, 2012; the Foundation for Science and Technology of Portugal, mobility grant SFRH/BSAB/114291/2016 (to JM); and iNOVA4Health - UID/Multi/04462/2013, a program financially supported by Fundacao para a Ciencia e Tecnologia/Ministerio da Educacao e Ciencia, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement.